Negative Allosteric Modulators of mGlu7 Receptor as Putative Antipsychotic Drugs - Cieślik, Paulina; Woźniak, Monika; Kaczorowska, Katarzyna; Brański, Piotr; Burnat, Grzegorz; Chocyk, Agnieszka; Bobula, Bartosz; Gruca, Piotr; Litwa, Ewa; Pałucha-Poniewiera, Agnieszka; Wąsik, Agnieszka; Pilc, Andrzej; et al. (Frontiers in Molecular Neuroscience, 2018)
The data concerning antipsychotic-like activity of negative allosteric modulators/antagonists of mGlu7 receptors are limited. The only available ligands for this receptor are MMPIP and ADX71743. In the present studies we used stable cell line expressing mGlu7 receptor and it was shown that both compounds dose dependently potentiated forskolin elevated cAMP concentration in the T-REx 293 cells, showing their inverse agonist properties. Subsequently, pharmacokinetic studies were performed. Both compounds were given i.p at the dose of 10 mg/kg. and reached Cmax 0.25-0.5 h after administration, and then they declined rapidly, ADX71743 being almost undetectable 2 h after administration, while the concentration of MMPIP was still observed, suggesting that the concentration of MMPIP was more stable. Finally, we investigated the role of both mGlu7 receptor NAMs in animal models of schizophrenia. Behavioral tests commonly used in antipsychotic drug discovery were conducted. Both tested compounds dose-dependently inhibited MK-801-induced hyperactivity (MMPIP at 15 mg/kg; ADX at 5 and 15 mg/kg) and DOI-induced head twitches (MMPIP at 5, 10, 15 mg/kg; ADX at 2.5, 5, 10 mg/kg). Moreover, the same effects were noticed in novel object recognition test, where MMPIP (5, 10, 15 mg/kg) and ADX71743 (1, 5, 15 mg/kg) reversed MK-801-induced disturbances. In the social interaction test antipsychotic activity was observed only for ADX71743 (5, 15 mg/kg). ADX71743 at the dose 2.5 mg/kg reversed MK-801-induced disruption in prepulse inhibition while MMPIP at 10 mg/kg reversed MK-801-induced disruption in spatial delayed alternation. The present studies showed that mGlu7 receptor ligands may be considered as a target for antipsychotic drugs, even though more studies are needed due to limited number of available ligands.